The effect of colchicine on cholesterol crystal formation, expansion and morphology: a potential mechanism in atherosclerosis - Abideen, Zain Ul; Pathak, Dorothy R.; Sabanci, Rand; Manu, Megan; Abela, George S. (Frontiers in Cardiovascular Medicine, 2024)
Background: Inflammation is pivotal to the progression of atherosclerosis. Cholesterol crystals (CCs) that grow and enlarge within the plaque core can cause plaque rupture, and trigger inflammation as they deposit into the atherosclerotic bed. Thus, agents that affect CC formation, expansion and morphology may reduce CV risk independent of lipid lowering and anti-inflammatory therapy.Objective: Because colchicine is highly concentrated in leukocytes that can enter the atherosclerotic plaque core, we tested its effect on the formation and growth of cholesterol crystals (CCs) in bench experiments to determine whether it may have direct effects on CCs, independent of its known anti-inflammatory actions.Method: Different dosages of colchicine mixed with cholesterol (0.05 -5 mg/ml/g of cholesterol) were used to influence the formation CCs and volume expansion in-vitro.These were compared to control samples with cholesterol in ddH2O without colchicine. In an ex-vivo study fresh atherosclerotic human plaques were incubated with and without colchicine in a water bath at 37ºC for 48 hours to assess the impact of colchicine on CC morphology. Scanning electron microscopy (SEM) was utilized to analyze CC morphology in samples from the various treatment groups.The addition of colchicine to cholesterol caused a substantial, dose-dependent reduction in volume (p<0.05). Pairwise comparisons of volume reduction, showed a significant reduction in volume at the 5mg/ml/g when compared to control (p<0.02) but the calculated Cohen's d, effect size was large for five of the six pairwise comparisons.By SEM CCs from both in-vitro and ex-vivo samples treated with colchicine had evidence of dissolution and changes in their morphology as evidenced by the loss of their sharp 3 edges. In contrast in CCs in untreated specimens retained their typical geometric structure.Colchicine can reduce CC formation and expansion and alter CC morphology. These previously unappreciated effects of colchicine may contribute to its clinical benefit in patients with CV disease independent of its anti-inflammatory effects.